VD_FINDINFO Décision / 2015 / 739 vom 30. September 2015 - VD Tribunal cantonal (2015)
RELIEF, DÉFAUTCONTUMACE, DÉCISION D'IRRECEVABILITÉ | 368 CPP (CH), 369 al. 1 CPP (CH), 369 al. 4 CPP (CH), 393 al. 1 let. b CPP (CH)